2020
DOI: 10.19044/esj.2020.v16n12p156
|View full text |Cite
|
Sign up to set email alerts
|

Composition Floristique, Diversité Et Structure Des Espèces Forestières Alimentaires De La Région De Sikasso Au Sud Du Mali

Abstract: The present work was launched to assess the floristic composition and structure of the native forest food species in order to tackle malnutrition. It was carried out in four natural forest from villages in two agro-ecological zones (two villages per agro-ecological zone) in southern Mali. In each natural forest, data were collected in 10 plots of 50 x 50 m using sampling systematic to one degree. In each plot, all tree were measured. Dendrometric data were collected on each tree (diameter at breast height or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
(6 reference statements)
2
6
0
1
Order By: Relevance
“…Madjimbé et al (2019) revealed in their research in the same area that the most important families are Fabaceae and Combretaceae. Regarding the highest number of genera per family and the most abundant species, these results corroborate the results of Saradoum (2012), Ndotam et al (2017) and Kouyate et al (2020). The latter, in their study found that species of the family Combretaceae, Poaceae, Fabaceae, Rubiacea and Apocynaceae were the most numerous and the most abundant species are Prosopis africana, Detarium microcarpum, Flueggea virosa, Piliostigma reticulatum and Anogeissus leiocarpa.…”
Section: -Discussion 4-1 Specific Composition Of the Pnmsupporting
confidence: 86%
See 1 more Smart Citation
“…Madjimbé et al (2019) revealed in their research in the same area that the most important families are Fabaceae and Combretaceae. Regarding the highest number of genera per family and the most abundant species, these results corroborate the results of Saradoum (2012), Ndotam et al (2017) and Kouyate et al (2020). The latter, in their study found that species of the family Combretaceae, Poaceae, Fabaceae, Rubiacea and Apocynaceae were the most numerous and the most abundant species are Prosopis africana, Detarium microcarpum, Flueggea virosa, Piliostigma reticulatum and Anogeissus leiocarpa.…”
Section: -Discussion 4-1 Specific Composition Of the Pnmsupporting
confidence: 86%
“…The larger the trees in a vegetation types, the less dense they are. Human pressure in woodland and tree savanna could be explained by the low presence of reproductive individuals due to abusive exploitation, especially of woody forest products (Kouyate et al, 2020). These results are confirmed by Diouf et al (2019) who indicate that the low basal area is explained by the presence of a strong community of small diameter reflecting a stand with shrub dominance.…”
Section: -2 Density and Stand Basal Areasmentioning
confidence: 58%
“…These results are confirmed by Kouyate et al (2020) in the woody formations of Sikasso, in southern Mali, with shannon diversity index of 4.99 and that of Giliba et al (2011) in the Miombo forest in Tanzania with Shannon diversity index of 4.27. The increasing demand for firewood and charcoal has not prevented the woody formation to be diversified.…”
Section: Preference and Forests Diversitysupporting
confidence: 56%
“…and 10.41% (in Kodialan co-occurring with Isoberlinia doka, Lannea acida, and Terminalia sp.) (Kouyaté et al 2020). This shows that the increasing frequency of the three main companion species Bombax costatum, Piliostigma thonningii, and Terminalia macroptera decreases regeneration of D. microcarpum.…”
Section: Density Of D Microcarpum and Accompanying Species In The Mbe Plainmentioning
confidence: 88%